Successive Convex Approximation for Efficient Energy Utilisation in Wireless Sensor Network - Bagyalakshmi, P; Anitha, R (International Journal of Computer Sciences and Engineering, 2025)
In traditional wireless sensor networks all the nodes communicate data with the central node. The path for data transmission is mainly the AODV protocol used. Each time the nodes communicate with each other before data transmission and the shortest path is selected to enable minimizing the battery usage in data transmission. This type of protocol uses considerable energy of all nodes in the network and the network traffic is increased at times depending on the number of nodes in the network. Convex approximation is introduced for overcoming this problem. In this method the nodes are grouped. Every group has a group head. Which determines the path for data transmission, also holding all the data about the nodes present under it. The group heads also communicate with other group heads to determine the path for data transmission.